Knowledge, attitude and practice of first aid among primary school teachers in Petaling Jaya, Malaysia - Mohd Yunos, Raihan (2021)
Introduction: Primary school children are very prone to injury and they spend more than half of their day in school. Every year, there will be cases of in-school injuries and children life is at risk. During school hours, the immediate guardian for the students will be the teachers and if anything goes wrong, teachers will be the front lines to the rescue, teachers act as a life saviour. A few seconds means life or death in a severe situation, with some basic first aid knowledge, teachers can help by giving the necessary help to reduce harm to the victim. According to the American Heart Association (2010), first aid is defined as the assessment and intervention given by a bystander or the victim himself with minimal or without medical equipment. Objective: This study aims to clarify the gap between knowledge, attitude, and practice of first aid among primary school teachers in Petaling Jaya, Selangor, Malaysia. Methodology: A cross-sectional quantitative survey was conducted from July to October 2017 among primary school teachers in Petaling Jaya, Selangor, Malaysia participants were selected using a clustered random sampling method. Data were collected using a pretested, structured self-administered questionnaire consisting of knowledge, attitude, and practice questions. Descriptive and chi-square analysis was done on the data by using statistical package for the social sciences (SPSS) version 25. Result: The study was conducted involving 124 participants from 3 selected primary schools in Petaling Jaya. Most of the participants were female (71.8%) and most had heard the term first aid before (98.4%). Almost half of the participants, 48.4% have good knowledge and 51.6% have poor knowledge. About 66.1% of participants had a positive attitude towards first aid. Most participants agree that bleeding is one of the most common injuries that need first aid. Most of the participants chose media (64.5%), books (62.9%) and family (40.3%) as their source of knowledge on first aid. There was a significant association between knowledge and training experience of the participants (p=0.045). Conclusion: The findings from this study would suggest more pieces of trainings for teachers to be more knowledgeable on first aid. In addition to that, knowledge of first aid should be widely spread through the media as well as through books as the participants prefer these sources concerning to first aid.